A Study On The Effect Of Hydrophobically Modified Cationic Acrylamide Copolymers On Flocculation Properties Of Kaolin Suspension - Lee , Khai Ern (2009)
A series of hydrophobically modified cationic polyacrylamides were synthesized via free radical solution copolymerization using ammonium persulphate/sodium hydrogen sulphite as the redox initiator.Satu siri kationik poliakrilamida hidrofobik terubah telah disintesis melalui larutan kopolimerasi radikal bebas dengan menggunakan ammonium persulfat/natrium hidrogen sulfit sebagai permula.